TANTANGAN PEMERINTAH ACEH DALAM MENGIMPLEMENTASI UNDANG-UNDANG PEMERINTAH ACEH (UUPA) - Januar, Eka; Marziah, Ainol (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
Prolonged conflict between the Free Aceh Movement (GAM) and the Indonesian government from 1976, until finally a settlement took place on 15 August 2005 in Helsinki, Finland, under the mediator Martti Ahtisaari (former President of Finland) both GAM-RI parties sat together to determine their position to end all causes of conflict in Aceh. In the points of the agreement of the Memorandum of Understanding (Helsinki MoU), Aceh was given special rights by the Government of Indonesia to administer Self Government. In the Helsinki MoU article 1 paragraph 1.1.2 a, b, c, d which plays a role in implementing the Law on the Governing of Aceh, but the reality that happened has not been as agreed upon in the MoU. The Aceh Government Law No 11 of 2006 which regulates the Aceh provincial government is further explained in the form of Qanun which was born by the Aceh Government. As a substitute for the Special Autonomy Law and the results of the peace agreement, Aceh is given special authority to regulate and manage government in accordance with the regulations of the Government of Aceh. The methodology of the research used is qualitative research with descriptive type. Searching for and analyzing data through interviews, observations and documents. This study used the theory of Power Balance. The Power Balance system provides various alternatives for policy makers, which leads to war or negotiations. The results of the research obtained are the factors that hampered the implementation of the UUPA, namely: aspects of the legal foundation, lack of cohesiveness of government in Aceh, the existence of internal and external factors, and different perceptions in understanding the Aceh Government Law